Influence of recovery time on post-activation potentiation in professional rugby players - Kilduff, L. P.; Owen, N.; Bevan, H.; Bennett, M.; Kingsley, M. I. C.; Cunningham, D. (Journal of Sports Sciences, 2008)
Following a bout of heavy resistance training, the muscle is in both a fatigued and potentiated state with subsequent muscle performance depending on the balance between these two factors. To date, there is no uniform agreement about the optimal acute recovery required between the heavy resistance training and subsequent muscle performance to gain performance benefits. The aim of the present study was to determine the recovery time required to observe enhanced muscle performance following a bout of heavy resistance training. Twenty professional rugby players performed a countermovement jump at baseline and ~15 s, 4, 8, 12, 16, 20, and 24 min after a bout of heavy resistance training (three sets of three repetitions at 87% one-repetition maximum squat). Power output, jump height, and peak rate of force development were determined for all countermovement jumps. Despite an initial decrease in countermovement jump performance after the heavy resistance training (P < 0.001), participants' performance increased significantly following 8 min recovery (P < 0.001) (i.e. jump height increased by 4.9%, s = 3.0). The findings suggest that muscle performance during a countermovement jump can be markedly enhanced following bouts of heavy resistance training provided that adequate recovery (~8 min) is allowed between the heavy resistance training and the explosive activity.